Bens públicos: da função social à outorga de uso compartilhado - Santana, Fabio Paulo Reis de (2024)
The research sought to demonstrate that the legal regime of sharing the use of public goods presents itself as a new legal tool available to the administrator, in addition to the types of use traditionally permitted by the legal system, because it allows the simultaneous use of public goods by public entities and privates always in the public interest. To this end, the study revisited the doctrine of public goods, analyzing the content of the main institutes and the most important theories on use, in order to establish the starting point of the investigation. Analyzing the transformations undergone by property, it was demonstrated that contemporary capitalism has conferred greater value on use at the expense of exchange capacity. Furthermore, the existence of a social function of public property was recognized, which leads to the conclusion that the underutilization of public property highlights a situation of unconstitutionality. The study also investigated the influence of the principle of efficiency and real estate subsidiarity of the Public Administration in shaping the duty to optimize use, in order to demonstrate, in sum of these principles, the contours of the social function of public goods, which guides maximum sustainable use of public goods. The research sought to lay the foundations for the introduction of the legal regime of shared use in the study of public goods, in order to allow a given good to be allocated to simultaneous use by public entities and privates, always in the public interest. Under this regime, the duty of sharing becomes possible as a mechanism for restricting the public property of others, in cases of unconstitutional underuse, as long as the social relevance of the intended use and the technical possibility are demonstrated social relevance of the intended use and technical and legal possibility of sharing. Thus, the study of public goods is extremely important because it establishes the conditions for the exercise of administrative competence by the State in achieving the objectives of the Republic